PENGARUH SELF CARE BEHAVIOR PENDERITA DIABETES MELLITUS TERHADAP NILAI ANKLE BRAKHIAL INDEKS (ABI) - Khotimah, Khotimah (Jurnal EDUNursing, 2017)
Abstract Diabetes Mellitus (DM) is a chronic disease that if not managed properly will cause various chronic complications. Peripheral arterial disorder is one of the complications of DM. The activities that support the management of DM well is with self care behavior. This study aims to determine the effect of self care behavior on the value of ankle barkhial index (ABI). The research design used was analytic correlation with cross sectional approach. The population in this study were all patients of DM in Unit Disease In RSUD Jombang as many as 100 respondents. The sample size is 60 respondents using simple random sampling technique. This research instrument uses self care inventory revised version and ABI SOP questionnaire. Data analysis using spearman rank test statistic. The result of the research is mostly (75%) of respondents of Self Care Behavior of DM patient is high of 45 respondents, almost all (76,6%) no complication of DM number 46  respondents, statistic test obtained p = 0,000, and r = 0,948. It shows that P <a (0,05), meaning there is influence Self Care Behavior to nili ABI, with very strong correlation coefficient. The better the DM patients do Self Care Behavior the smaller the complications that occur. The importance of self-care behavior will control blood sugar levels in the body so as to prevent the possibility of complications of DM.  Keywords: Self Care Behavior, diabetes, ABI